”If you don't care you’ll die” : The Concept of “Liveness” in Arnold Wesker’s Chicken Soup with Barley and John Osborne’s Look Back in Anger - Sarah-jane Coyle (Theatre Academy)
The phenomenological concept of “liveness” has a long-standing relationship with theatre and performance studies. This relationship has primarily been limited to questions of ontology; namely, what constitutes the ephemeral nature of theatre and what counts as “liveness” in performance in an increasingly digitised age. By contrast, this article will consider “liveness” as a doctrine and pervasive ideology in two landmark plays of 1950s Britain, Arnold Wesker’s Chicken Soup with Barley, and John Osborne’s Look Back in Anger. Both plays represent dramas of emotion and were written by members of the “angry young men” movement, a term denoting a group of working-class dramatists, who used their work to express frustration with Britain’s outdated class system and post-war society. By employing close reading alongside literary and historical analysis, this article will argue that the “anger” of the angry young men is not just a descriptor for disaffected liberals but is part of a wider movement in these plays emphasising the importance of embodying “liveness” and vitality as a means of resisting the standardised culture of everyday capitalist life.